Bioactive Properties of Persea americana Peel Extract and Their Role in Hypercholesterolemia Management and Cardiovascular Health - Laura M. Teixeira; Catarina P. Reis; Rita Pacheco (Foods)
Cardiovascular diseases remain the leading cause of death worldwide, with hypercholesterolemia being a major contributing risk factor. Although cholesterol-lowering drugs are widely available, concerns about several adverse side effects have increased the demand for natural alternatives, with the most common approaches involving the incorporation of foods rich in bioactive compounds into the diet. To explore this growing interest in food-based strategies for cardiovascular health, this study formulated and evaluated an aqueous peel extract of Persea americana to assess its potential role as a complementary approach to managing hypercholesterolemia. The extract was characterized, revealing the presence of various bioactive compounds, including pyridoxine-O-Hex, which was identified for the first time in a P. americana extract component. The safety profile of the extract was confirmed through in vivo assessment. Furthermore, the extract demonstrated protective effects against oxidative stress in HepG2 cells. Additionally, permeability studies using Caco-2 cells, as a model of the gastrointestinal barrier, indicated that the extract effectively reduced cholesterol’s permeation. In summary, these findings suggest that P. americana peel extract may serve as a promising natural product for functional foods for cardiovascular health and hypercholesterolemia management.